Expression of the chloroplast genome: modern concepts and experimental approaches - M. G. Siniauskaya; N. G. Danilenko; N. V. Lukhanina; A. M. Shymkevich; O. G. Davydenko (Вавиловский журнал генетики и селекции)
A unique feature of plants is the presence of two extranuclear genomes, chloroplasts and mitochondria. The chloroplast genome is relatively small, 100–120 genes, which encode less than 5 % of all proteins required for plastids to function. The cpDNA expression retains prokaryotic features, cotranscription in the operon, bacteria-like RNA polymerases and promoters, 70S ribosomes etc., also new characters appear such as uncoupling of transcription with translation, phage-type RNA polymerases, RNA editing, and splicing of primary transcripts. The interaction of the nucleus (nuclear genomes) and cytoplasm (plastid and mitochondrial genes) during plant development is necessary for proper development and adaptation to the environment. The aim of this review is to disclose the peculiarities of plastid genome expression. The way the genetic information in chloroplasts is used (transcription, editing, splicing, polyadenylation and translation) is consequently described. Furthermore, the importance of all expression machinery components in plant life is discussed. Modern approaches for RNA pool study are described and critical points of nuclear-cytoplasmic interaction in the functions of chloroplasts are revealed. The information about the most important factors of nuclear-cytoplasmic signaling in higher plants (sigma factors and PPR proteins encoded by the nucleus) are reviewed. Thus, the multilevelness and viability of plastid genome expression regulation in plant cells and interdependence of the processes in different compartments is proved. A summary of the latest studies of the expression of the plastid genome using genetic chips (microarrays, macroarrays) is provided. Original results are presented.